Isolamento de vírus gigantes em biomas brasileiros - Talita Bastos Machado (2021)
The discovery of the first giant amoeba-associated virus described in 2003, called Acanthamoeba polyphaga mimivirus (APMV), has spurred a growing search for new giant viruses resulting in the discovery of several other groups that currently make up the group of Large Nucleocytoplasmic DNA Viruses (NCLDVs) . Although the interest in those viruses has grown in recent years, little is known about their diversity and distribution in nature, as well as their ecological and phylogenetic relationships. Knowing the importance of isolating new viruses to expand our knowledge about the virosphere, this work aimed to carry out prospecting studies in samples as fresh water, salt water, soil, mud and sewage, collected from different Brazilian biomes. Those samples were inoculated in cultures of amoebas of the species Acanthamoeba castellanii aiming for virus isolation. Further identification of the new isolates were performed by transmission and scanning electron microscopy images. A total of 641 aliquots were processed from 163 samples collected in the states of Amazonas, Bahia, Goiás, Maranhão, Mato Grosso do Sul, Minas Gerais, Piauí, Rio Grande do Sul, Santa Catarina and São Paulo, covering all Brazilian biomes : Cerrado (57.57%), Atlantic Forest (30.89%), Caatinga (3.12%), Amazon (3.12%), Pampa (1.5%), Pantanal (0.62%), in addition to samples with the unidentified biome. Among them, 459 aliquots were obtained from fresh water (71.6%), 60 from salt water (9.4%), 2 from soil (0.3%), 10 from mud (1.6%) and 110 from sewage (17.2%). A total of 67 new isolates were obtained (isolation rate of 10.45%), belonging to at least 5 different viral groups: 13 Mimiviruses, 26 Marseilleviruses, 1 Pandoravirus, 9 Cedratviruses, 3 Yaraviruses and 15 Pithoviridae-like. This isolation method was effective, since new isolates were obtained from all types of samples and from all biomes tested, in addition to having isolated several viral groups, with different morphologies and sizes, including a completely new virus in the virosphere, the Yaravirus. In comparison with other similar studies, the present work obtained a greater richness of isolated groups in A. castellanii, most of which were representatives of the Marseilleviridae family. The findings of this work demonstrate how important prospection studies are for the expansion of knowledge about the virosphere, since the isolation of new viruses helps us to understand the diversity, distribution and richness of amoeba viruses in nature, as well as contribute to studies related to the replication cycle and phylogeny.